Why is the measured maximum lift in wind tunnels dependent on the measurement method?. Issue 3 (September 2020) - Olsen, A S; Sørensen, N N; Bak, C; Gaunaa, M; Mikkelsen, R; Fischer, A; Beckerlee, J; Ildvedsen, S
Abstract: The present study investigates the differences in the predicted lift for a wind tunnel model from either surface pressures or side wall pressures. The investigated model is the NACA63-418 tested in the Poul la Cour tunnel. The measurements are compared with previous conducted wind tunnel campaigns for a Reynolds number of 3E6. The 3D CFD model of the wind tunnel will be used for investigating details of the flow mechanisms, and to validate assumptions and findings from the experimental data. The CFD simulations show that when the flow is attached the lift based on the side wall pressures results in almost the same lift as calculated from the surface pressures. Around the maximum lift and in the stalled region the flow is not anymore 2D. For the NACA63-418 airfoil the lift based on the side wall pressures are generally highest. The CFD simulations confirm that the method used to predict the lift from the limited side wall pressure strips in the wind tunnel is applicable.